2013
DOI: 10.1371/journal.pone.0065227
|View full text |Cite
|
Sign up to set email alerts
|

An Ethanolic Extract of Lindera obtusiloba Stems, YJP-14, Improves Endothelial Dysfunction, Metabolic Parameters and Physical Performance in Diabetic db/db Mice

Abstract: Lindera obtusiloba is a medicinal herb traditionally used in Asia for improvement of blood circulation, treatment of inflammation, and prevention of liver damage. A previous study has shown that an ethanolic extract of Lindera obtusiloba stems (LOE) has vasoprotective and antihypertensive effects. The possibility that Lindera obtusiloba improves endothelial function and metabolic parameters in type 2 diabetes mellitus (T2DM) remains to be examined. Therefore, the aim of the present study was to determine the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 60 publications
1
10
0
Order By: Relevance
“…Indeed, exposure of endothelial cells (ECs) to circulating MPs from acute coronary syndrome patients induced premature endothelial senescence and thrombogenicity through activation of the Ang II/AT1R/NADPH oxidase pathway [ 13 ]. Such findings are in good agreement with observations indicating that the angiotensin system contributes to the induction of endothelial dysfunction in the inner curvature of the aortic arch [ 14 ], in experimental models of atherosclerosis and aging, hypertension, diabetes and in patients at high cardiovascular risk [ 15 17 ]. ECs express angiotensin-converting enzyme (ACE) that stimulates the conversion of angiotensin I (Ang I) into the biologically active Ang II [ 18 ], which, in turn, causes NADPH oxidase-mediated oxidative stress and promotes vasoconstriction, endothelial senescence and dysfunction, and vascular and cardiac remodeling [ 19 , 20 ].…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…Indeed, exposure of endothelial cells (ECs) to circulating MPs from acute coronary syndrome patients induced premature endothelial senescence and thrombogenicity through activation of the Ang II/AT1R/NADPH oxidase pathway [ 13 ]. Such findings are in good agreement with observations indicating that the angiotensin system contributes to the induction of endothelial dysfunction in the inner curvature of the aortic arch [ 14 ], in experimental models of atherosclerosis and aging, hypertension, diabetes and in patients at high cardiovascular risk [ 15 17 ]. ECs express angiotensin-converting enzyme (ACE) that stimulates the conversion of angiotensin I (Ang I) into the biologically active Ang II [ 18 ], which, in turn, causes NADPH oxidase-mediated oxidative stress and promotes vasoconstriction, endothelial senescence and dysfunction, and vascular and cardiac remodeling [ 19 , 20 ].…”
Section: Introductionsupporting
confidence: 91%
“…The angiotensin system is a major contributor to endothelial dysfunction observed prematurely at atheroprone arterial sites at risk, and also in aging- and major cardiovascular disease-related endothelial dysfunction such as coronary artery disease [ 14 17 ]. The angiotensin system promotes vascular pro-oxidant, pro-atherothrombotic and pro-senescence responses, and contributes to MPs shedding [ 7 , 8 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown a pivotal role of both circulating and local angiotensin systems in the induction of endothelial dysfunction in several experimental models of hypertension, atherosclerosis, diabetes, and aging [4,6,[8][9][10] and also in humans [11]. Angiotensin II (Ang II)-induced endothelial dysfunction is characterized by the vascular formation of ROS subsequent to the upregulation of the expression level of NADPH oxidase [12,13], thereby promoting eNOS uncoupling to further generate ROS [14], alteration of calcium-dependent K + channels involved in EDH responses [15], and increased expression of COXs, promoting EDCF responses [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenesis of DM vascular lesions is relative to vascular endothelial cell injury, platelet activation and the abnormality of coagulation and fibrinolysis ( 1 ). Endothelial cell injury is a vital early manifestation of DM vascular disease and is the initiating factor in the development of atherosclerosis ( 2 , 3 ). Therefore, the improvement of vascular endothelial function is crucial for the treatment of DM.…”
Section: Introductionmentioning
confidence: 99%